Pain management in interventional radiology - Ray, Charles E.; Cambridge eBooks (Cambridge : Cambridge University Press, 2008)
As interventionalists become more involved with patients as care providers rather than solely as proceduralists, understanding and treating pain is a vital part of daily practice. This book provides an overview of the multiple techniques used in the management of pain in interventional radiology suites. Topics include techniques for the treatment and prevention of pain caused by interventional procedures, as well as minimally invasive techniques used to treat patients with chronic pain symptoms. Approximately half of the book is dedicated to the diagnosis and treatment of spinal pain; other chapters focus on intraprocedural and post-procedural pain management, embolization and ablation techniques used to treat patients with uncontrollable pain, and alternative treatments for pain relief. This book is a practical resource for anyone looking to acquire skills in locoregional or systemic pain control and wishing to improve the quality of life for patients undergoing procedures or suffering from disease-related pain.
Pain management in interventional radiology : an introduction / Jason R. Bauer and Charles E. Ray, Jr. -- Clinical evaluation of low-back pain / Anthony P. Dwyer, Curt Freudenberger, and Vikas V. Patel -- Local anesthetics / Jan Namyslowski -- Functional lumbar spine anatomy : a review / Anthony P. Dwyer [and others] -- Percutaneous vertebroplasty / Mitchell T. Smith and Charles E. Ray, Jr. -- Kyphoplasty / Frances D. Faro, Anthony P. Dwyer, and Vikas V. Patel -- Epidural steroid injections / Brian D. Petersen, Kirkland W. Davis, and James Choi -- Selective nerve root blocks / Brian Petersen, Kirkland W. Davis, and James Choi -- Discography / Charles E. Ray, Jr. and Leo J. Rothbarth -- Facet (zygapophyseal) joint injections / Nick Stence -- Articular interventions in pain management : a general approach / Blaze Cook -- Percutaneous management of visceral pain / Frank Morello -- Embolization of painful neoplasms / Jennifer R. Huddleston and Stephen P. Johnson -- Image-guided ablation of painful osteolyses / David T. Wang and Charles E. Ray, Jr. -- Chronic pelvic pain in women / Derek L. West -- Sedation and analgesia medications / George Behrens, Hector Ferral, and Nilesh H. Patel -- Guidelines for sedation administered by nonanesthesiologists / Iftikhar Ahmad -- Pediatric sedation for radiological imaging studies and interventions / Keira P. Mason -- Nontraditional pain management in interventional radiology / Salomao Faintuch [and others] -- Postprocedural pain control / Stan Zipser.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Interventional radiology; Analgesia; Electronic books